2009
DOI: 10.1080/19317610902922537
|View full text |Cite
|
Sign up to set email alerts
|

Transpeople, Transprejudice and Pathologization: A Seven-Country Factor Analytic Study

Abstract: Eight hundred and forty one undergraduate students in seven countries (China, Malaysia, Singapore, Thailand, Philippines, United Kingdom and United States) completed a questionnaire examining perceptions of transwomen (on a transacceptance-transprejudice continuum). The aim was to identify factors underlying transacceptance-transprejudice, and relationships among them. Five factors were identified (MENTAL-ILLNESS, DENIAL-WOMEN, SOCIAL-REJECTION, PEER-REJECTION, SEXUAL-DEVIANCE). MENTAL-ILLNESS (the belief that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 67 publications
5
64
0
3
Order By: Relevance
“…Davies and Hudson [12] compared attitudes of heterosexual men and women when considering rape of men and transgender people; they found that men blamed the transgender victims more, and considered rape of a transgender person less severe. Transphobia is also highly correlated with homophobia [42,52], and males tend to also be more homophobic than females [25,31,32,42,57].…”
Section: Transphobia In Malesmentioning
confidence: 97%
See 1 more Smart Citation
“…Davies and Hudson [12] compared attitudes of heterosexual men and women when considering rape of men and transgender people; they found that men blamed the transgender victims more, and considered rape of a transgender person less severe. Transphobia is also highly correlated with homophobia [42,52], and males tend to also be more homophobic than females [25,31,32,42,57].…”
Section: Transphobia In Malesmentioning
confidence: 97%
“…The presence of a transgender person in a public bathroom that matches their gender identity may be viewed as crossing a societal boundary, and can cause other & Rebecca J. Stones rebecca.stones82@gmail.com bathroom users to question which other boundaries that transgender person might cross, raising questions of safety and privacy. Other bathroom users, particularly those unfamiliar with transgender people, might question or protest a transgender person's presence in the bathroom, possibly arguing that they're not really the gender they claim to be [5,17,57] or that transgender people are inherently unsafe [46]. Security or the police might be contacted, or a transgender person might be accosted by members of the public in the vicinity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interview and survey studies reveal that transgender people themselves perceive high rates of serious manifestations of GIB, including employment discrimination and interpersonal rejection and harassment in the workplace (e.g., Budge et al, ; Dietert & Dentice, ; Grant et al, ; Grossman & D'Augelli, ; Lombardi, ; Nemoto, Bödeker, & Iwamoto, ; Whittle, Turner, Al‐Alami, Rundall, & Thom, ). Correlational studies have used self‐report measures to assess the general public's attitudes toward the transgender community as a group (e.g., Case & Stewart, ; Gazzola & Morrison, ; Hill & Willoughby, ; Landén & Innala, ; Norton & Herek, ; Winter et al, ). For example, a large survey ( N = 2,281) revealed that heterosexual U.S. adults’ attitudes toward transgender people were significantly more negative than their attitudes toward homosexual and bisexual people (Norton & Herek, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large survey ( N = 2,281) revealed that heterosexual U.S. adults’ attitudes toward transgender people were significantly more negative than their attitudes toward homosexual and bisexual people (Norton & Herek, ). Similarly, a survey of undergraduate students in seven countries revealed strongly negative attitudes toward transgender women, and these attitudes were driven by the belief that transgender women were mentally ill (Winter et al, ). While these studies suggest that GIB is pervasive, their correlational design precludes drawing definitive conclusions about the causes of bias experienced by the transgender community.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the United Kingdom, the United States and across Asia has shown that the belief that trans people are mentally ill is the most powerful underlying factor linked to transprejudice [76]. At this point in time, the World Health Organisation is in a position to make a real difference to the lives of trans people, not only in terms of care and treatment, but also in terms of their happiness and human rights.…”
Section: The Only Ethical Way Ahead: Complete Removal From the Icd-11mentioning
confidence: 99%